Penerapan Metode Data Mining Market Basket Analysis Terhadap Data Penjualan Produk Pada Toko Iblite Luxury Menggunakan Algoritma Apriori - Anggi Canita Simanjuntak; Miranda Elisabet Sitanggang; Muhairoh Indah Cahyani; Nita Syahputri (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Data mining is a technique to dig up new information from a data warehouse, information is seen as very important and valuable because by mastering information it is easy to achieve a goal, this makes everyone compete to obtain information, as well as in trading businesses such as the Iblite Luxury store. This store is located in Medan close to residents' houses, Sales transaction data will continue to grow, causing data storage to be even larger. Sales transaction data is only used as an archive without being properly utilized. Basically, a dataset has very useful information. Market basket analysis with a priori algorithm is one of the data mining methods that aims to find association patterns based on consumer shopping patterns, so that it can be known what items of goods are purchased in a At the same time, the results of this study found that the highest support and confidence values were Ysl and Chanel with a support value of 50% and confidence of 75%.